2011
DOI: 10.1002/smll.201100845
|View full text |Cite
|
Sign up to set email alerts
|

Colloidally Stable Silicon Nanocrystals with Near‐Infrared Photoluminescence for Biological Fluorescence Imaging

Abstract: Luminescent silicon nanocrystals (ncSi) are showing great promise as photoluminescent tags for biological fluorescence imaging, with size-dependent emission that can be tuned into the near-infrared biological window and reported lack of toxicity. Here, colloidally stable ncSi with NIR photoluminescence are synthesized from (HSiO1.5)n sol-gel glasses and are used in biological fluorescence imaging. Modifications to the thermal processing conditions of (HSiO1.5)n sol-gel glasses, the development of new ncSi oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
99
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 65 publications
1
99
0
Order By: Relevance
“…It has been shown that ligand-stabilized nanocrystals can be easily tuned to emit from the near-UV (NUV) through visible (VIS) to the near-IR (NIR) region with varying size and surface. These advantages make it an ideal material for solution processable applications [2832]. However, the story does not end here.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ligand-stabilized nanocrystals can be easily tuned to emit from the near-UV (NUV) through visible (VIS) to the near-IR (NIR) region with varying size and surface. These advantages make it an ideal material for solution processable applications [2832]. However, the story does not end here.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 During lithium insertion, however, silicon undergoes volume expansion -including the fourfold increase in unit cell volume observed in the case of Li 22 Si 5 . 3 This reversible expansion and contraction with repeated cycling results in crack formation and disintegration of the electrode leading to loss of conductivity, decrease in specific capacity and short cycle life of the battery.…”
Section: Introductionmentioning
confidence: 97%
“…Steric stabilization strategies typically use long poly(ethylene glycol) chains to achieve colloidal stability. The use of solid lipid nanoparticles by Henderson et al and phospholipid micelles by Erogbogbo et al are prime examples 13, 14, 15. Electrostatic stabilization strategies rely on ionic ligands to prevent flocculation, commonly used ones include olefins with terminal carboxylic acids and terminal primary amines 8, 12, 15, 16, 17, 18, 19, 20.…”
Section: Introductionmentioning
confidence: 99%